Marketing Practices Among Sari-Sari Stores in Dapitan City: Basis for Proposed Extension Program - Pagara, Edelyn E. (Future Science / FSH-PH Publications, 2022)
This study aimed to determine the different marketing practices employed among sari-sari store owners in Dapitan City during the Calendar Year 2020. It used a descriptive research method utilizing a questionnaire as the principal tool for gathering data. The data were statistically treated using frequency counting, percent, weighted mean, standard deviation, and Mann-Whitney Test. The study's findings revealed that sari-sari store owners in Dapitan City had the same marketing practices focusing on process and people. Customers of the sari-sari stores had the same observation on the marketing practices of sari-sari store owners in Dapitan City, which focus on people and place. It was found that sari-sari store owners and customers had different perspectives or views on marketing practices. It was recommended that sari-sari store owners and potential sari-sari store owners attend training and seminars aiming to improve their marketing practices in coordination with the Department of Trade and Industry and the Local Government Unit of Dapitan. Further, customers are encouraged to give their feedback on the marketing practices of the sari-sari store owners, and researchers are encouraged to conduct a separate study on this matter.